Incidence, Risk Factors, and Clinical Implications of Subarachnoid Hyperdensities on Flat-Panel Detector CT following Mechanical Thrombectomy in Patients with Anterior Circulation Acute Ischemic Stroke - Serrallach, Bettina L.; Branca, Mattia; Mujanovic, Adnan; Boronylo, Anna; Hanke, Julie M.; Hakim, Arsany; Pilgram-Pastor, Sara; Piechowiak, Eike I.; Gralla, Jan; Meinel, Thomas; Kaesmacher, Johannes; Dobrocky, Tomas (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Flat-panel detector CT immediately after mechanical thrombectomy can detect complications, including early hemorrhagic transformation and subarachnoid hyperdensities. The clinical significance of subarachnoid hyperdensities in patients undergoing mechanical thrombectomy remains unclear.MATERIALS AND METHODS: We studied 223 patients who underwent mechanical thrombectomy for anterior circulation stroke who had flat-panel detector CT performed immediately after the procedure and had follow-up imaging within 24 hours. Subarachnoid hyperdensity severity was categorized into 5 grades (subarachnoid hyperdensities, 0: absent to subarachnoid hyperdensities, IV: extensive). Baseline and procedural characteristics as well as outcome measures were analyzed using group comparisons and multivariable logistic regression analyses.RESULTS: Overall, 100/223 (45%) patients showed subarachnoid hyperdensities on immediate postinterventional flat-panel detector CT. The factors associated with an increased subarachnoid hyperdensity risk were the following: medium-vessel occlusion or distal-vessel occlusion compared with a large-vessel occlusion, a more distal device position, a higher number of device passes, a larger volume of contrast applied, worse final reperfusion expanded TICI, and after receiving IV thrombolysis. The occurrence of subarachnoid hyperdensity grades II–IV was independently associated with worse functional outcomes (adjusted OR for mRS, 3–6: 2.2; 95% CI 1.1–4.3), whereas patients with subarachnoid hyperdensity grade I had outcomes similar to those in patients without subarachnoid hyperdensities.CONCLUSIONS: Our study identified risk factors for subarachnoid hyperdensities, most of which reflect increasingly challenging procedures or more peripheral recanalization attempts. The presence of subarachnoid hyperdensity grades II–IV was associated with poorer outcomes, suggesting the need for personalized strategies to reduce its incidence and severity or potentially improve recovery after subarachnoid hyperdensities.aORadjusted ORDVOdistal-vessel occlusioneTICIexpanded TICIFDCTflat-panel detector CTLVOlarge-vessel occlusionMTmechanical thrombectomyMVOmedium-vessel occlusionSHsubarachnoid hyperdensities